2008
DOI: 10.1182/blood-2008-03-140830
|View full text |Cite
|
Sign up to set email alerts
|

Unrelated donor umbilical cord blood transplantation for inherited metabolic disorders in 159 pediatric patients from a single center: influence of cellular composition of the graft on transplantation outcomes

Abstract: Outcomes of 159 young patients with inherited metabolic disorders (IMDs) undergoing transplantation with partially HLA-mismatched unrelated donor umbilical cord blood were studied to investigate the impact of graft and patient characteristics on engraftment, overall survival (OS), and graft-versus-host disease (GVHD). Patients received myeloablative chemotherapy (busulfan, cyclophosphamide, ATG) and cyclosporine-based GVHD prophylaxis. Infused cell doses were high (7.57 ؋ 10 7 /kg) because of the patients' you… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

16
211
2
7

Year Published

2013
2013
2015
2015

Publication Types

Select...
4
2
1

Relationship

2
5

Authors

Journals

citations
Cited by 242 publications
(237 citation statements)
references
References 43 publications
16
211
2
7
Order By: Relevance
“…The safety and efficacy of UCBT from unrelated donors was similar to that reported by previous studies (Staba et al 2004;Martin et al 2006;Prasad et al 2008). However, this is the only comprehensive prospective longitudinal study on a large cohort of patients with Hurler syndrome who were evaluated before and after transplanta- Fig.…”
Section: Discussionsupporting
confidence: 82%
See 3 more Smart Citations
“…The safety and efficacy of UCBT from unrelated donors was similar to that reported by previous studies (Staba et al 2004;Martin et al 2006;Prasad et al 2008). However, this is the only comprehensive prospective longitudinal study on a large cohort of patients with Hurler syndrome who were evaluated before and after transplanta- Fig.…”
Section: Discussionsupporting
confidence: 82%
“…Somatic disease was evaluated at various departments at Duke University, University of North Carolina, or University of Minnesota. The transplant data of all the patients were previously reported (Prasad et al 2008;Orchard et al 2010). This study was reviewed by the institutional review board of the University of North Carolina at Chapel Hill.…”
Section: Patient Characteristicsmentioning
confidence: 99%
See 2 more Smart Citations
“…The lower enzyme activity in the heterozygous donor cells may have impacted on the efficacy of enzymatic cross-correction, as has been demonstrated for MPS I (Wynn et al 2009). Indeed, a more recent study suggested a moderate positive effect of UCBT on CNS disease in MPS III patients, with a more prominent effect in patients that were transplanted at a younger age (Prasad et al 2008).…”
Section: Introductionmentioning
confidence: 99%